Effect of orthokeratology on precision and agreement assessment of a new swept-source optical coherence tomography biometer - Bao Shu; Fangjun Bao; Giacomo Savini; Weicong Lu; Ruixue Tu; Haisi Chen; Benhao Song; Qinmei Wang; Jinhai Huang (Eye and Vision, 2020)
Abstract Background To evaluate the effect of orthokeratology on precision of measurements in children using a new swept-source optical coherence tomography (SS-OCT) optical biometer (OA-2000), and agreement between its measurements and those provided by the commonly used IOLMaster based on partial coherence interferometry (PCI). Methods This study recruited fifty-one eyes of 51 normal children (8–16 years). An operator took measurements with the two biometers. Then, a second operator took measurements with the SS-OCT biometer. After orthokeratology was performed for one month, the same operators repeated the same procedures. Axial length (AL), mean keratometry (Km) at 2.5 mm and 3.0 mm diameters (Km2.5 and Km3.0), central corneal thickness (CCT), anterior chamber depth (ACD), lens thickness (LT) and corneal diameter (CD) were analyzed. Results With the SS-OCT optical biometer, the test-retest repeatability of AL measurements was < 0.06 mm. For all parameters, the coefficients of variation were < 1.23% and the intraclass correlation coefficients were > 0.95. The 95% limits of agreement of difference between the two devices for CD parameter were up to 1.53 mm. After orthokeratology, the fluctuation ranges of difference for Km3.0 measurement was 1.11 times higher than before orthokeratology, while the absolute values of difference for AL, Km2.5, ACD and CD measurements were comparable. Conclusions Before and after orthokeratology, the SS-OCT biometer showed high repeatability and reproducibility for all measurements. Wearing orthokeratology contact lenses affected the agreement between SS-OCT and PCI biometers for Km3.0 measurements. The CD measurement showed poor agreement between the two devices.